2009
DOI: 10.1021/ef800984v
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Order Model Based on Principal Component Analysis for Process Simulation and Optimization

Abstract: It is well-known that distributed parameter computational fluid dynamics (CFD) models provide more accurate results than conventional, lumped-parameter unit operation models used in process simulation. Consequently, the use of CFD models in process/equipment co-simulation offers the potential to optimize overall plant performance with respect to complex thermal and fluid flow phenomena. Because solving CFD models is time-consuming compared to the overall process simulation, we consider the development of fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 22 publications
(25 reference statements)
2
38
0
Order By: Relevance
“…However, the heat transfer in the boiler is highly non-linear with respect to the coal feed rate and/or oxygen concentration. Lang et al [34] employed a principal component analysis (PCA) with a neural network mapping technique to develop the ROMs to interpolate the flow field inside a gasifier and results with satisfying fidelity were obtained. However, this approach is quite complicated in its mathematical form.…”
Section: The Rom Developmentmentioning
confidence: 99%
“…However, the heat transfer in the boiler is highly non-linear with respect to the coal feed rate and/or oxygen concentration. Lang et al [34] employed a principal component analysis (PCA) with a neural network mapping technique to develop the ROMs to interpolate the flow field inside a gasifier and results with satisfying fidelity were obtained. However, this approach is quite complicated in its mathematical form.…”
Section: The Rom Developmentmentioning
confidence: 99%
“…Lastly, reduced order models (ROM) have become fashionable in recent years. Especially notable are Lang et al (2009), who deduced ROMs from CFD simulations. The only disadvantages here are the expensive set-up procedure and the small area of applicability.…”
Section: Existing Strategies For Model Reductionmentioning
confidence: 99%
“…The order reduction can be achieved through multivariate analysis techniques as in principal component analysis (PCA) or proper orthogonal decomposition. [124][125][126][127][128]. Alternatively a computationally expensive model can be replaced by lower dimensional surrogate model obtained through fitting of experimental or simulated data using techniques such as kriging, response surface methodology (RSM), artificial neural networks (ANN) or high dimensional model representation (HDMR) [12,[129][130][131][132][133][134].…”
Section: Reduced Order Modelsmentioning
confidence: 99%
“…However these models are computationally expensive to evaluate and thus may not be useful for simulation and optimization purposes. Reduced order modeling based on principal component analysis was introduced by Lang et al [128] for the co-simulation of CFD models with unit operation models for process equipment. Boukouvala et al [110] have shown that the same approach can be applied to the reduction of DEM data for use in solids process models.…”
Section: Comparison Of Hdmr Rsm Kriging and Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation